Comparison of ZnS(Ag) Scintillator and Proportional Counter Tube for Alpha Detection in Thin-Layer Chromatography - Marc Pretze; Jan Wendrich; Holger Hartmann; Robert Freudenberg; Ralph A. Bundschuh; Jörg Kotzerke; Enrico Michler (Pharmaceuticals)
(1) Background: Targeted alpha therapy is an emerging field in nuclear medicine driven by two advantages: overcoming resistance in cancer-suffering patients to beta therapies and the practical application of lower activities of 212Pb- and 225Ac-labelled peptides to achieve the same doses compared to beta therapy due to the highly cytotoxic nature of alpha particles. However, quality control of the 212Pb/225Ac-radiopharmaceuticals remains a challenge due to the low activity levels used for therapy (100 kBq/kg) and the formation of several free daughter nuclides immediately after the formulation of patient doses; (2) Methods: The routine alpha detection on thin-layer chromatograms (TLC) of 212Pb- and 225Ac-labelled peptides using a MiniScanPRO+ scanner combined with an alpha detector head was compared with detection using an AR-2000 scanner equipped with an open proportional counter tube. Measurement time, resolution and validity were compared for both scanners; (3) Results: For 225Ac, the quality control values of the radiochemical purity (RCP) were within the acceptance criteria 2 h after TLC development, regardless of when the TLC probe was taken. That is, if the TLC probe was taken 24 h after radiosynthesis, the true value of the RCP was not measured until 5 h after TLC development. For 212Pb-labelled peptides, the probe sampling did not have a high impact on the value of the RCP for the MiniScanPRO+ and AR-2000. A difference was observed when measuring TLC with the AR-2000 in different modes; (4) Conclusions: The MiniScanPRO+ is fast, does not require additional equipment and can also measure the gamma spectrum, which may be important for some radiopharmaceutical production sites and regulatory authorities. The AR-2000 has a better signal-to-noise ratio, and this eliminates the need for additional waiting time after TLC development.